Classification and Dynamics of Class of Î¾(as)-QSO - Izzat Qaralleh; Ahmad Termimi Ab Ghani; Hamza Abd Hamza Abd El-Qader (Institute for Research and Community Services (LPPM) ITB, 2020)
The current study provides a new class of Î¾(as)-QSO defined on 2D simplex and classifies it into 18 non-conjugate (isomorphic) classes. This classification is based on their conjugacy and the remuneration of coordinates. The current study also examines the limiting points associated with the behavior of trajectories for four classes defined on 2D simplex.